2021
DOI: 10.19261/cjm.2021.841
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Radical Scavenging Activity of the Extracts from Deschampsia Antarctica É. Desv. Plants Grown in Situ and in Vitro

Abstract: The work was aimed at studying the phytochemicals available in D. antarctica plants from various sites on Antarctic Islands, introducing the plants into in vitro culture and comparing the extracts from the plants grown in situ and in vitro. All the extracts were found to contain high amount of phenols, with luteolin and hydroxybenzoic acids derivatives being the main phytochemicals in the extracts from the plants grown in situ and in vitro. Being diluted by 10 times, the extracts scavenged 50÷90% of DPPH• radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In extracts of plants grown in vitro, the amount of flavonoids decreased as compared to in situ plants, from ~75 to ~50% of the total weight of polyphenols, while the amount of phenolic acids increased, respectively. For in situ plant extracts studied previously (Ivannikov et al 2021) and in this work, the mass fraction of flavonoids derivatives was on average ~75%. Data on the correlation between the content of phenols and content of flavonoids in the samples D1-D12 (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation

Polish Polar Research

Ivannikov,
Anishchenko,
Kuzema
et al. 2022
“…In extracts of plants grown in vitro, the amount of flavonoids decreased as compared to in situ plants, from ~75 to ~50% of the total weight of polyphenols, while the amount of phenolic acids increased, respectively. For in situ plant extracts studied previously (Ivannikov et al 2021) and in this work, the mass fraction of flavonoids derivatives was on average ~75%. Data on the correlation between the content of phenols and content of flavonoids in the samples D1-D12 (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…The dominance of flavonoids among the polyphenols of D. antarctica was typical only for the plants grown in natural conditions. Ivannikov et al (2021) showed in a study devoted to the comparison of extracts from D. antarctica plants grown in situ and in vitro that such extracts differ by the ratio of the compounds belonging to the three main registered groups of polyphenols (flavonoids and their derivatives; simple phenols/hydroxybenzoic acids and their derivatives; hydroxycinnamic acids and their derivatives). In extracts of plants grown in vitro, the amount of flavonoids decreased as compared to in situ plants, from ~75 to ~50% of the total weight of polyphenols, while the amount of phenolic acids increased, respectively.…”
Section: Discussionmentioning
confidence: 99%

Polish Polar Research

Ivannikov,
Anishchenko,
Kuzema
et al. 2022
“…Tricin, as well as other flavonoids (orientin, luteolin and its derivatives), phenolic compounds, hydroxybenzoic and hydroxycinnamic acids were also detected by other resear chers in the D. antarctica plants grown in situ and in vitro [23].…”
Section: Resultsmentioning
confidence: 86%
“…C 11 H 10 O 5 ( p -Coumaroyl glycolic acid), C13H12O8 ( p -Coumaroyl tartaric acid)), flavonoids and their derivatives (e.g. C 15 H 8 O 5 (Coumestrol), C 15 H 14 O 5 (Tetrahydroxyfla van/Tetrahydroxy dihydroxychalcone)), and other compounds, such as fatty acids [ 49 ]. Overall, the prominent feature of second-derivative spectra detected in the frequency ranges of 1118–1098 cm −1 , 1240–1160 cm −1 , 1377 cm −1 , and 3750–3000 cm −1 could be attributed to the comparatively high contents of chitin, phenols, flavonoids, and other fatty acids in the ornithogenic soils of Ardley Island.…”
Section: Resultsmentioning
confidence: 99%